Silent cerebral lesions and cognitive function after pulmonary vein isolation with an irrigated gold-tip catheter: REDUCE-TE Pilot study - Schmidt, B.; Széplaki, G.; Merkely, B.; Kautzner, J.; Driel, V.; Bourier, F.; Kuniss, M.; Bulava, Alan; Nolker, G.; Khan, M.; Lewalter, T.; Klein, N.; et al. (Wiley-Blackwell, 2019)
Introduction Stroke is one of the most feared complications during catheter ablation of atrial fibrillation (AF). While symptomatic thromboembolic events are rare, magnetic resonance imaging (MRI) may identify asymptomatic (ie, silent) cerebral lesions (SCLs) following pulmonary vein isolation (PVI) procedures. Methods and Results The REDUCE-TE Pilot was a prospective multicenter, single-arm observational study investigating the incidence of SCL in patients with symptomatic paroxysmal AF undergoing PVI with a novel gold-tip, externally irrigated ablation catheter. After ablation, cerebral diffusion-weighted MRI and a postablation follow-up were performed at 1 to 3 days after the ablation procedure. A neurocognitive test was done before and after ablation. The primary study endpoint was the occurrence of one or more new SCLs. Secondary study endpoints included neurocognitive status, procedural success rate, and periprocedural complications including symptomatic thromboembolic events. A total of 104 patients were enrolled (69% male, mean age: 61.5 +/- 9.7 years, mean CHA(2)DS(2)-VASc score: 1.7 +/- 1.2). Postprocedural MRI examination was performed in 97 patients, and in nine of them (9.3%; 95% CI: 4.3-16.9%) a total of 11 SCLs were detected. Univariate analyses did not reveal any significant predictor for new SCLs. Nonsignificant trends were observed for low activated clotting time during ablation and for international normalized ratio value outside the range of 2 to 3 at ablation. There was no evidence of significant deterioration of neurocognitive function after PVI. In four patients, a pericardial tamponade was noted but all patients fully recovered during follow-up. Conclusions Ablation of AF using a novel gold-tip, externally irrigated ablation catheter, resulted in SCLs in approximately one out of 10 patients without a measurable effect on neurocognitive function.
Keywords: ablation; atrial fibrillation; cognitive function; gold-tip catheter; irrigated catheter; pulmonary vein isolation; silent cerebral embolism